2017
DOI: 10.3390/su9050803
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Rebound Effect for the Construction Industry: Empirical Evidence from China

Abstract: Abstract:As the largest energy consumer and carbon emitter, China has made substantial efforts to improve energy efficiency to save energy, while the energy rebound effect mitigates its effectiveness. This paper is based on the logical relationship among capital input, technical change, economic growth, and energy consumption, adapting an alternative estimation model to estimate the energy rebound effect for the construction industry in China. Empirical results reveal that the average energy rebound effect for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As a result, the maximum possible resource saving through increased efficiency is not achieved; the direct rebound effect reduces, negates, or even exceeds the benefits of improved technological efficiency [34]. Related empirical studies have analyzed direct rebound effects in energy consumption in the company context [35,36] or in various consumer fields such as electricity [34], residential heating [37][38][39], residential cooling [40], or residential lighting [41,42]. For instance, studies investigating the rebound effect of fuel prices on vehicle miles traveled found that direct rebound effects regularly occur, varying between 10-30% [43,44].…”
Section: Rebound Effects As Negative Environmental Effectsmentioning
confidence: 99%
“…As a result, the maximum possible resource saving through increased efficiency is not achieved; the direct rebound effect reduces, negates, or even exceeds the benefits of improved technological efficiency [34]. Related empirical studies have analyzed direct rebound effects in energy consumption in the company context [35,36] or in various consumer fields such as electricity [34], residential heating [37][38][39], residential cooling [40], or residential lighting [41,42]. For instance, studies investigating the rebound effect of fuel prices on vehicle miles traveled found that direct rebound effects regularly occur, varying between 10-30% [43,44].…”
Section: Rebound Effects As Negative Environmental Effectsmentioning
confidence: 99%
“…It is assumed that energy efficiency improvements derive from technological progress, thus it is first necessary to calculate its contribution to economic growth-σt in Eq (15) below. A neoclassical production function is considered in Eq (2) as a starting point (Griffin, 1981;Howarth, 1997 andDu, Qiang, Li andBai, 2017),…”
Section: Direct Rebound Effectmentioning
confidence: 99%
“…Besides the macroeconomic level, some scholars analyzed the energy rebound effects from the perspective of specific industries. Their analysis found that all the rebound effect values of China's construction industry [26,27], steel industry [28], light industry [29], manufacturing industry [30], and six energy-intensive industries [18] are greater than 0, showing different degrees of partial rebound effect or backfire effect. Lin et al [31] used the LMDI method and the TFP model to measure the rebound effect of the Chinese nonferrous metals industry and pointed out that the average rebound effect value from 1985 to 2014 was about 0.8302 and showed a downward trend, indicating that improving the energy utilization level will become an important way to save energy and reduce emissions.…”
Section: Full Rebound Effect Re =mentioning
confidence: 99%